Final-Year EFL Student’s Perceptions of ChatGPT in Teaching Competency Development - Ahmad Wira Yudha; Khusnul Khatimah; Dzul Rachman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study explores the perceptions of final-year students majoring in English Education regarding ChatGPT in supporting the development of teaching competencies as artificial intelligence (AI) technologies become increasingly integrated into educational practices. Understanding its impact on future educators is of paramount importance. Utilizing a descriptive qualitative approach, data were collected through semi-structured interviews conducted with English Education students at Universitas Muhammadiyah Kalimantan Timur (UMKT). The findings reveal that ChatGPT serves as a valuable tool for improving lesson planning, enriching instructional materials, and enhancing classroom management strategies. The students expressed positive attitudes toward ChatGPT's ability to generate creative ideas, clarify complex topics, and serve as an easily accessible learning aid. However, concerns regarding excessive reliance on AI as well as the importance human-centered teaching approaches were highlighted. This research contributes to the understanding of how AI technologies like ChatGPT can be effectively utilized in EFL teacher training programs to balance technological advancements.